Budget impact analysis of dexamethasone intravitreal implant for the treatment of diabetic macular oedema - Fernando de Andrés-Nogales; Enrique Cervera; Félix Armadá; Luis Arias; Itziar Oyagüez; Concha Martínez (Elsevier, 2018)
Abstract: Objective: To assess the economic impact following the inclusion of an intravitreal implant of dexamethasone for the treatment of diabetic macular oedema in a healthcare area in Spain. Method: A 3-year budget impact model was designed to estimate healthcare direct costs for adult patients with diabetic macular oedema from the National Health System perspective. The approved therapies in use (aflibercept/ranibizumab/dexamethasone) were considered. The target population was estimated from published diabetic macular oedema prevalence (6.41%) and incidence (0.82%) for a population of 25,000 adults. Dexamethasone was assumed to be used annually in 20%, 30% and 40% of patients, respectively. Annual total costs included: drug acquisition (based on frequency of injections per every year, considering exfactory prices with mandatory deduction and split of vials), intravitreal administration, patient monitoring, management of cardiovascular and ocular adverse events (cataracts, increased intraocular pressure, endophthalmitis, vitreous haemorrhage and retinal detachment). Detailed resource consumption reflecting clinical practice was provided from local experts in retina and vitreous. Unitary costs (€, 2016) were obtained from national databases and literature. Sensitivity analyses were performed to assess model robustness. Results: The inclusion of intravitreal dexamethasone implant would lead to annual cost savings of €35,030 (-4.2%), €10,743 (-1.8%) and €5,051 (-0.9%), years 1-3 respectively. Total costs were reduced mainly by the fewer annual injections required by dexamethasone. The average annual incremental costs were -€350, -€96 and -€41 per patient. Conclusions: The inclusion of an intravitreal dexamethasone implant for the treatment of diabetic macular oedema would lead to cost-savings for the considered health area, mainly by reducing the administration costs.